Assessment of the Impact of the Crisis on New PPI Projects : Update Six - World Bank (Washington, DC, 2012)
Investment commitments to new infrastructure projects with private participation (PPI projects) reaching closure in developing countries grew by 15 percent in the fourth quarter of 2009 compared with the same period of 2008-and by 15 percent in 2009 as a whole. These growth rates indicate a strong recovery from the 45 percent drop in investment commitments in the second half of 2008 compared with the same period of 2007. But investment continued to grow selectively, concentrated in large energy projects in a few countries-Brazil, China, India, and Turkey. The crisis continues to affect new PPI activity. Some planned projects are still being delayed, restructured, or, to a lesser extent, canceled. Transport continues to be the most affected sector, Europe and Central Asia the most affected region, and low-income countries the most affected country income group. Despite the more difficult environment, developing country governments remain committed to their public-private partnership (PPP) programs, as confirmed by the number of new projects that were being tendered, awarded, or restructured in the fourth quarter of 2009. Commercial bank lending remains constrained, and the choices of investors and financiers continue to reflect the 'flight to quality.' For projects able to raise financing, the conditions are more stringent, with a higher cost of debt, lower debt/equity ratios, shorter tenors, and more conservative structures. But the impact of the crisis has varied across countries, depending on whether there is an active local financial market and whether the government has taken proactive measures to foster liquidity.